Exposure to benzene and childhood leukaemia: a pilot case-control study. Issue 2 (26th February 2013) - Lagorio, Susanna; Ferrante, Daniela; Ranucci, Alessandra; Negri, Sara; Sacco, Paolo; Rondelli, Roberto; Cannizzaro, Santina; Torregrossa, Maria Valeria; Cocco, Pierluigi; Forastiere, Francesco; Miligi, Lucia; Bisanti, Luigi; et al.
Abstract : Objectives: Main purpose To evaluate the feasibility of a measurement-based assessment of benzene exposure in case-control studies of paediatric cancer; Additional aims To identify the sources of exposure variability; to assess the performance of two benzene biomarkers; to verify the occurrence of participation bias; to check whether exposures to benzene and to 50 Hz magnetic fields were correlated, and might exert reciprocal confounding effects. Design: Pilot case-control study of childhood leukaemia and exposure to benzene assessed by repeated seasonal weekly measurements in breathing zone air samples and outside the children's dwellings, with concurrent determinations of cotinine, t-t -muconic acid (MA) and sulfo-phenylmercapturic acid (S-PMA) in urine. Participants: 108 cases and 194 controls were eligible for inclusion. Results: Full-participation was obtained from 46 cases and 60 controls, with low dropout rates before four repeats (11% and 17%); an additional 23 cases and 80 controls allowed the collection of outdoor air samples only. The average benzene concentration in personal and outdoor air samples was 3 μg/m 3 (SD 1.45) and 2.7 μg/m 3 (SD 1.41), respectively. Personal exposure was strongly influenced by outdoor benzene concentrations, higher in the cold seasons than in warm seasons, and not affected by gender, age, area of residence or caseness. Urinary excretion of S-PMA and personal benzene exposure were well correlated. Outdoor benzene levels were lower among participant controls compared with non-participants, but did not differ between participant and non-participant cases; the direction of the bias was found to depend on the cut-point chosen to distinguish exposed and unexposed. Exposures to benzene and extremely low-frequency magnetic fields were positively correlated. Conclusions: Repeated individual measurements are needed to account for the seasonal variability in benzene exposure, and they have the additional advantage of increasing the study power. Measurement-based assessment of benzene exposure in studies of childhood leukaemia appears feasible, although it is financially and logistically demanding.